Sturktur dan Unsur Kebahasaan Teks Deskripsi Kelas VII SMP Negeri 7 Bukittinggi - Resti Melysa; Emidar; Ermawati Arief; Herlin Triana (Paedagogie, 2026)
The purpose of this study is first, to describe the structure of descriptive texts written by seventh-grade students of SMP Negeri 7 Bukittinggi. Second, to describe the linguistic elements of descriptive texts of seventh-grade students of SMP Negeri 7 Bukittinggi. This type of research is qualitative research with descriptive methods. The data in this study are descriptive texts of seventh-grade students of SMP Negeri 7 Bukittinggi. The data sources in this study are seventh-grade students of SMP Negeri Bukittinggi in the 2025/2026 academic year. The research instrument is the researcher herself and the performance instrument is the context of writing descriptive texts. The data collection technique in this study is the fishing technique. The data validation technique used in this study is the triangulation technique. The data analysis technique is first, identifying data according to the concept or theory of structure and linguistic elements. Second, identifying data based on the reference theory. Third, analyzing data by recording sentences related to the linguistic elements of descriptive texts. Fourth, interpreting the analyzed data. Fifth, concluding the results of the data description by writing a report. The results of this study consist of two. First, in writing descriptive texts, seventh-grade students of SMP Negeri 7 Bukittinggi have used three text structures. The three text structures are identification/general description, description of parts and conclusion. This is evident from the 30 descriptive texts that have been analyzed, there are 13 complete descriptive texts using identification/general description, description of parts and conclusion. 30 texts that have an identification/general description structure, 30 texts that have a description of parts structure, and 13 texts that have a conclusion structure. Second, seen from the linguistic aspect, seventh-grade students of SMP Negeri 7 Bukittinggi still have errors. This is evident from the 372 sentences analyzed, there are 325 sentences and EYD that are incorrect. This can be seen from 55 errors in the pattern of incorrect sentence elements, 307 errors in the use of incorrect capital letters. 47 errors in inappropriate prepositions, 20 errors in the pronouns ku, kau, ku, mu, and -nya, and 40 errors in incorrect punctuation.